The strange case of SN 2011ja and its host. Issue Volume 9:Issue S296(2013) (29th January 2014) - Chakraborti, Sayan; Ray, Alak; Smith, Randall; Ryder, Stuart; Yadav, Naveen; Sutaria, Firoza; Dwarkadas, Vikram V.; Chandra, Poonam; Pooley, David; Roy, Rupak
Abstract: SN 2001ja was observed twice in three months using the Chandra X-Ray Observatory. The X-ray flux could be due to interaction with the circumstellar medium, perhaps dominated by the reverse shock heated thermal plasma, or from inverse Compton scattering at the forward shock. In both cases, for a steady wind-like circumstellar density profile, the X-ray flux is expected to fall off as a power law or faster. But the flux from the position of SN 2011ja, increased by a factor of three between these observations. In this presentation, we investigated possible reasons, including contamination from other astrophysical sources such as a X-Ray Binary, within the Chandra's resolution, in the host galaxy using our observations, modelling and pre-explosion Chandra/XMM data.